2023
DOI: 10.3390/s23083975
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dynamic Plantar Pressure and Influence of Clinical-Functional Measures on Their Performance in Subjects with Bimalleolar Ankle Fracture at 6 and 12 Months Post-Surgery

Abstract: Recovery after ankle fracture surgery can be slow and even present functional deficits in the long term, so it is essential to monitor the rehabilitation process objectively and detect which parameters are recovered earlier or later. The aim of this study was 1) to evaluate dynamic plantar pressure and functional status in patients with bimalleolar ankle fracture 6 and 12 months after surgery, and 2) to study their degree of correlation with previously collected clinical variables. Twenty-two subjects with bim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(100 reference statements)
1
0
0
Order By: Relevance
“…A study of dynamic plantar pressure changes at 6 and 12 months after bilateral ankle fracture surgery showed that AFG patients had lower plantar pressure (peak and mean) and longer contact time than did CG patients and that AFG patients had significantly lower e-cadence and gait speed than did the control group. Similarly, (Fernández-Gorgojo et al, 2023), Zhu et al (2022) reported similar results in a study of 12 subjects after trimalleolar fracture; i.e., abnormal changes in plantar pressure were mainly manifested in the forefoot and hindfoot regions. Compared with those in the healthy control group, the patients in the symptomatic group had shorter step lengths, larger step widths, slower walking speeds, shorter single supports and obvious asymmetry in gait; these authors believe that these differences might be related to functional impairment of the anterior tibial and peroneal longus muscle ability.…”
Section: Ankle Fracturesupporting
confidence: 60%
“…A study of dynamic plantar pressure changes at 6 and 12 months after bilateral ankle fracture surgery showed that AFG patients had lower plantar pressure (peak and mean) and longer contact time than did CG patients and that AFG patients had significantly lower e-cadence and gait speed than did the control group. Similarly, (Fernández-Gorgojo et al, 2023), Zhu et al (2022) reported similar results in a study of 12 subjects after trimalleolar fracture; i.e., abnormal changes in plantar pressure were mainly manifested in the forefoot and hindfoot regions. Compared with those in the healthy control group, the patients in the symptomatic group had shorter step lengths, larger step widths, slower walking speeds, shorter single supports and obvious asymmetry in gait; these authors believe that these differences might be related to functional impairment of the anterior tibial and peroneal longus muscle ability.…”
Section: Ankle Fracturesupporting
confidence: 60%